Environmental education through an app for the quantification of the carbon footprint (Research, Society and Development, 2021)
Along with the increase in quality of life levels around the world, there are increases in comfort demands (use of air-conditioning, for example), and meeting these demands results in higher energy consumption. In parallel there is an environmental awareness process emerging, propelled by concerns related to the consumption of fossil fuels and rational use of energy. Public buildings and homes are responsible for the majority of energy consumption in Brazil. This study presents the development of an application (app) for smartphones and computers. The objective is to promote awareness on the consumption of electricity, in a rational, efficient and sustainable way. The application of the Life Cycle Assessment methodology provided the carbon footprint associated with the consumption of 1 kWh of electricity from the national grid. This result was introduced within the app, which provides the carbon footprint (kg CO2-eq) associated with the consumption of electricity, estimated from the user’s habits.